Secondary metabolites: deterring herbivores - Wink, Michael (Encyclopedia of life sciences, 2001)
Secondary metabolites that can interfere with basic molecular targets of animals or microbes provide plants with protection against herbivores and/or microbes, since plants cannot run away when attacked by herbivores and do not have an immune system to defend themselves against microbes.
Gesehen am 06.10.2017